Stabilizing unstable biomechanical model to understand sitting stability for persons with spinal cord injury. Issue 2 (2020) - Guerra, Thierry-Marie; Blandeau, Mathias; Nguyen, Anh-Tu; Srihi, Hajer; Dequidt, Antoine
Abstract: This paper deals with the stabilization of a new open-loop unstable non-linear biomechanical model to represent a person living with a spinal cord injury. The computational complexity of the model when using the Takagi-Sugeno formalism is increased compared to previous models which is a source of difficulty to find a control law. Several solutions are presented combining robustness, and model simplification from previous works in the form of linear matrix inequalities (LMI) which are then solved using convex optimization technics. Finally, simulations results are presented to show the validity and the effectiveness of different approaches.